Women And Islamic Education Reform In Lombok Island: Study at Syaikh Zainuddin NW Anjani Islamic Boarding School and Darul Mujahidin NW Mataram Islamic Boarding School - Hilmi Sopian; Suprapto Suprapto (Pelopor Publikasi Akademika, 2023)
Women are creatures of Allah SWT who cannot be underestimated because the presence of women is often a problem in the world of Islamic educationin chili, role limitations are an ongoing problem besides that Islamic education is stillface various fluctuations and this can be caused by various factors, including social norms, economic limitations, and the perception that women should play a role in the domestic sphere. In the view of Islam itself, women have an honorable and noble position in the view of Islam. Even women can feel equality and justice. Islam upholds the values ??of humanity, justice, equality and nobility. And this is what is needed in the reform of Islamic education in the world of education, especially Islamic boarding schools in Lombok. Islamic Education Reform at Syaikh Zainuddin NW Anjani Islamic Boarding School and Darul Mujahidin NW Mataram Islamic Boarding School has been able to answer questions and existing problems with several breakthroughs: firstly providing women's access to Islamic education, secondly providing influence and breakthroughs in Islamic education reform towards women's empowermentin the neighborhood Islamic boarding school. Besides this, Islamic boarding schools still have challenges that must be found solutions for the realization of reformeducation sustainable and able to elevate the achievements of Islamic boarding schools on the island of Lombok in the eyes of the world.